2020
DOI: 10.1097/pas.0000000000001564
|View full text |Cite
|
Sign up to set email alerts
|

DDIT3 Immunohistochemistry Is a Useful Tool for the Diagnosis of Myxoid Liposarcoma

Abstract: Myxoid liposarcoma is a malignant adipogenic neoplasm characterized by prominent arborizing capillaries, occasional lipoblasts, and primitive-appearing spindle cells in a myxoid background. A recurrent translocation in myxoid liposarcoma results in an oncoprotein consisting of full-length DDIT3 (CHOP) fused to an N-terminal segment of either FUS (TLS) or, less often, EWSR1. Here, we explore the diagnostic significance of DDIT3 expression in myxoid liposarcoma using a mouse monoclonal antibody recognizing an ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 20 publications
5
38
0
Order By: Relevance
“…Our findings strongly support the conclusions of Scapa et al 20 . that diffuse nuclear DDIT3 expression can be clinically very useful to definitively confirm the diagnosis of MLPS, whereas negative staining can be used to argue strongly against MLPS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings strongly support the conclusions of Scapa et al 20 . that diffuse nuclear DDIT3 expression can be clinically very useful to definitively confirm the diagnosis of MLPS, whereas negative staining can be used to argue strongly against MLPS.…”
Section: Discussionsupporting
confidence: 91%
“…One key issue in the optimisation of antibodies for diagnostic use is the need to develop criteria for positive and negative staining that are both reproducible and optimise the balance between sensitivity and specificity. When they used a cut‐off of >50% cells being positive in a mixed TMA and whole section cohort, Scapa et al 20 . found a sensitivity of 100% (46 of 46 tumours from 36 patients), as compared with our sensitivity of 96%, and a specificity of 100% (254 of 254 patients), the same as our specificity of 100%.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Very recently, immunohistochemistry for DDIT3 (DNA Damage-Inducible Transcript 3) has emerged as a useful surrogate for molecular testing. Scapa et al reported DDIT3 positivity in 46/46 cases of myxoid liposarcoma and only limited weak expression in other tumors [56]. Minimal staining was observed in cases of dedifferentiated liposarcoma (15%) and solitary fibrous tumor (25%), possibly due to the proximity of DDIT3, MDM2 and STAT6 on chromosome 12.…”
Section: Ddit3 In Myxoid Liposarcomamentioning
confidence: 99%